Solution of fisher's equation using Daftardar-Gejji and Jafari Method (DJM) / Nur Hidayah Masni Abdullah and Mat Salim Selamat - Abdullah, Nur Hidayah Masni; Selamat, Mat Salim (2015)
In this article, the Jafari and Daftardar-Gejji method (JDM) is applied to obtain power series solutions to Fisher's equation. Comparison with the other iterative methods such as Adomian decomposition method and variational iteration method show that the DIM method is powerful method for nonlinear diffusion equations.